EVALUASI KEBIJAKAN PERLINDUNGAN PEKERJA MIGRAN INDONESIA (PMI) DI KABUPATEN SUMEDANG OLEH DINAS TENAGA KERJA DAN TRANSMIGRASI KABUPATEN SUMEDANG - Rakhadyanata, Ridanadya (JRPA - Journal of Regional Public Administration, 2025)
This study aims to determine the Evaluation of the Policy for the Protection of Indonesian Migrant Workers (PMI in Sumedang Regency by the Sumedang Regency Manpower and Transmigration Office. The background of this research is based on the problem of Indonesian Migrant Workers (PMI) departing nonprocedurally, complaints of problematic workers abroad, and low public understanding regarding the protection mechanism for Indonesian Migrant Workers (PMI). The research method used in this study is a qualitative approach with a descriptive type of research. The determination of samples/informants in this study was carried out using purposive sampling, namely 4 people. Data collection techniques are carried out through literature studies and field studies through (observation, interviews and documentation) and triangulation. After that, data processing uses data collection, data reduction, data presentation and verification. The results of the study show that the implementation of the Indonesian Migrant Workers (PMI) protection policy by the Sumedang Regency Manpower and Transmigration Office has been running, but it is not optimal. In general, the implementation of the program is in accordance with Law Number 18 of 2017 through verification, briefing, socialization, monitoring, and cross-agency collaboration. However, obstacles are still found such as the lack of direct socialization to the community, budget limitations, and non-procedural departures. On the other hand, this policy has provided benefits in the form of increasing public knowledge and awareness as well as a sense of security for Indonesian Migrant Workers (PMI). The impact evaluation also showed a positive impact through a decrease in the number of complaints and an increase in legal departures. This study suggests that the Sumedang Regency Manpower and Transmigration Office expand the scope of direct socialization to the village community, build an integrated information system across agencies, and strengthen the role of the village government in supporting the implementation of the comprehensive Indonesian Migrant Workers (PMI) protection policy.